First Occurrence Of Leptoglossus Crassicornis (Dallas) (Heteroptera: Coreidae) In Chile, With A Key To The Species Of Leptoglossus Guérin-Méneville Recorded In The Country - Faundez Peña, Eduardo Ivan; LOPEZ-ALISTE M; Carvajal Morales, Mariom Adriana (My University, 2018)
The presence of the leaf-footed bug Leptoglossus crassicornis (Dallas, 1852) is reported for the first time in Chile. Specimens were collected in Valparaiso and Metropolitan of Santiago regions. Eriosyce senilis coimasensis (F. Ritter) Katt. is recorded for the first time as host plant for L. crassicornis, confirming its association with Cactaceae. The significance of this record is discussed and a key to the species of Leptoglossus recorded so far from Chile is included.
Primera cita de Leptoglossus crassicornis (Dallas) (Heteroptera: Coreidae) en Chile, con clave para las especies de Leptoglossus Guérin-Méneville registradas en el país
Keywords: Hemiptera; Coreinae; Anisoscelini; faunistics